Song Form and the Mainstreaming of Hip-Hop Music - Duinker, Ben (Current Musicology, 2021)
Song form in North American hip-hop music has evolved along the genre’s journey from its origins as a live musical practice, through its commercial ascent in the 1980s and 1990s, to its dominance of mainstream popular music in the 21st century. This paper explores the nature and evolution of song form in hip-hop music and uses them as a musical lens to view the gradual and ongoing mainstreaming of this genre. With the help of a corpus of 160 hip-hop songs released since 1979, I describe and unpack section types common to hip-hop music—verses, hooks, and instrumentals—illustrating how these sections combine in different formal paradigms, such as strophic and verse-hook. I evaluate the extent to which formal structures in hip-hop music can be understood as products of the genre’s live performance culture; one with roots in African American oral vernacular traditions such as toasting. Finally, I discuss how form in hip-hop music has increasingly foregrounded the hook (chorus): the emergence of the verse-hook song form, an increase in sung hooks (often by singers outside the hip-hop genre), the earlier arrival of hook sections in songs, and the greater share of a song’s duration occupied by hooks. Viewing hip-hop music’s evolution through this increasing importance of the hook provides a clear representation of the genre’s roots outside of, and assimilation into, mainstream popular music; one of many Black musical genres to have traversed this path (George, 1988).